European Rail Traffic Management System – An Overview - Abed, Dr Sajed K (Iraqi Journal for Electrical and Electronic Engineering, 2010)
This paper aims to give an overview of the European Rail Traffic Management System (ERTMS) which is currently being implemented in Europe and other parts of the world. It provides some background on this system, the objectives behind the development of the ERTMS, its architecture, different application levels of the ERTMS and brief information on its implementation in Europe and worldwide. The paper assumes the readers have a little or no knowledge of the ERTMS.